NILAI INDEKS KONDISI DARI IKAN SIGANUS JAVUS BERDASARKAN HASIL TANGKAPAN NELAYAN DI PERAIRAN JUATA KOTA TARAKAN - Salim, Gazali (Jurnal Harpodon Borneo, 2013)
Siganus javus is one type of fish that has a lot of potential that is still not fully utilized where these fish contain protein which is high at around 69.2% (weight of wet) and 18.5% (weight of dry). The research objective is to analyze biotechnical of condition index of Siganus javus. Methods of research using descriptive method. The scope of this study is the variable of condition index of Siganus javus. Data collection techniques using survey. Techniques of sampling Siganus javus using sampling with purposive sampling method. Capture as much as 12 times the sampling, each taking a maximum of 10 fish due to sampling of endemik is taking place so rarely found. The results percentage of the value of the model index condition Siganus javus for male sex is body shape of flattenedobtained by 47.46%, body shape of ideal/proportion of 5.08%, body fat of 47.46%, and than while the female sex of condition index percentage obtained flattened body shape amounting to 60.98%, proportional body shape by 2.44%, the body fat of 31.71% and body shape are very fat at 4.88%.Keywords : condition index, Siganus javus, Juata Waters of Tarakan